Functional properties optimization of protein mixtures in a model system - Cáñez-Carrasco, María Guadalupe; Cumplido-Barbeitia, Luis Germán; Orduño-Fragoza, Oralia; Corella-Madueño, María Alba Guadalupe (Acta Universitaria, 2016)
Cornell’s (1990) mixtures design was used to formulate three-component mixture systems: pig meat protein extract soluble in saline solution (PCC), serum protein concentrate (SPC) and bovine plasma (PB). The objective was to study ingredients interaction effects on functional properties of protein mixtures in a prototype system. Gel strength variable and emulsifying activity index showed a linear effect in mixtures, due to presence of PCC and the three components, respectively. A negative interaction between PCC • CPS and PCC • PB was noticed. In water retention capacity only effect of PCC presence was found. Loss of protein in water released from gels after compression linearly increased due to addition of CPS, showing a positive interaction of CPS • PB. In the emulsifying activity index there was a linear effect of the three components and a negative interaction of PCC • CPS and PCC • PB. Ingredients interactions in mixture properties were significant.